The Role of Parental Acceptance/Rejection in the Development of Internet Addiction among Adolescence - Shahana Mumtaz; Fozia Aamir Siddiqui; Muniza Malik (Progressive Research Journal of Arts & Humanities (PRJAH), 2023)
The present study was aimed at investigation parents’ acceptance or rejection in the development of internet addiction among young adolescence. It was a co-relational study; survey method was used for data collection. There were two hypotheses in the study. 1. Maternal and paternal rejection would be significant predictors of internet addiction among young adolescence.2. Male and female students would significantly differ on internet addiction. Sample of the study comprised of 844 young adolescence including 389 male students, and 455 female students. Participants of the study was collected from three universities of Jamshoro District. The age range of participants was between 16 to 28 years. For the measurement of variables Parental Rejection and Internet Addiction three valid and reliable tools were administered on the sample of the study: 1. Parental acceptance / Rejection questionnaire. First, Internet addiction tests; second, Adult PARQ and control: Mother and Father, Personality Assessment Questionnaire; and third Questionnaire about the demographical variables of the respondents. Results of Hierarchical multiple regression analysis indicate that both maternal and paternal rejection are strong predictors of internet addiction F (1, 842) = 32.62, p = < .001, and paternal rejection predicts internet addiction more strongly than maternal rejection. t (1,841.90) = 4.72, p = < .001, with a small effect size of r = .16. Over all the study indicates a string role of parental rejection in the development of internet addiction among young adolescence.